2014
DOI: 10.1007/978-3-319-09614-8_22
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mouse Models for Alcohol Metabolism, Toxicity, and Cancer

Abstract: Alcohol abuse leads to tissue damage including a variety of cancers; however, the molecular mechanisms by which this damage occurs remains to be fully understood. The primary enzymes involved in ethanol metabolism include alcohol dehydrogenase (ADH), cytochrome P450 isoform 2E1, (CYP2E1), catalase (CAT), and aldehyde dehydrogenases (ALDH). Genetic polymorphisms in human genes encoding these enzymes are associated with increased risks of alcohol-related tissue damage, as well as differences in alcohol consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 81 publications
2
19
0
Order By: Relevance
“…1 and 2). Therefore, we examined the effect of PXR deficiency, binge EtOH, and their interaction on mRNAs of Adh1, Adh4, Aldh2, and Aldh1a1 as well as the protein levels of ADH1, CYP2E1, and ALDH1A1, which are known to be involved in EtOH metabolism (Heit et al, 2015). The EtOH treatment had a significant effect on mRNA levels of hepatic Adh1, Adh4, and Aldh2 (P 5 0.001) but not the genotype or their interaction.…”
Section: Resultsmentioning
confidence: 99%
“…1 and 2). Therefore, we examined the effect of PXR deficiency, binge EtOH, and their interaction on mRNAs of Adh1, Adh4, Aldh2, and Aldh1a1 as well as the protein levels of ADH1, CYP2E1, and ALDH1A1, which are known to be involved in EtOH metabolism (Heit et al, 2015). The EtOH treatment had a significant effect on mRNA levels of hepatic Adh1, Adh4, and Aldh2 (P 5 0.001) but not the genotype or their interaction.…”
Section: Resultsmentioning
confidence: 99%
“…For example, studies in mouse models and non-human primates suggest that alcohol consumption in young adult females adversely affects oocyte quality and early stages of embryogenesis, even when alcohol consumption ceases before the completion of fertilisation and pregnancy42,43. Experimental evidence from animal models and on oocytes from women treated for infertility also suggest that maternal obesity may affect oocyte quality44.…”
Section: Mendelian Randomization Assumptions and Assessing Causal Intmentioning
confidence: 99%
“…The studies available suggest that ethanol increases ROS through two parallel and reinforcing mechanisms. Normal alcohol metabolism is known to generate ROS as a result of ethanol oxidation (Figure ) (Ceni, Mello, & Galli, ; Dennery, ; Heit et al, ; Mello, Ceni, Surrenti, & Galli, ). In support of these observations, Reinke and collaborators showed that in vivo exposure to ethanol increased the formation of free radicals (Reinke, Lai, DuBose, & McCay, ).…”
Section: The Etiology Of Fasdmentioning
confidence: 99%